Impact of Pre-and Post-harvest Technological Interventions and Social Mobilization on Area-Expansion of Mango in Tribal area of Odisha - Singh, H.S. (Indian Journal of Extension Education, 2013)
Mango based horticulture was promoted as a livelihood option as early as in seventies in Kashipur block of Rayagada  district in Odisha but quite a few tribals took it seriously. Technological interventions over the period of eight years by  experts made mango orchards commercial and paved the way for significant increase in mango area in the tribal villages.  Fruit fly management, hot water treatment (HWT), fruit packing and transportation as pre and post harvest interventions  and social mobilization through village meetings and orchard management were attempted regularly from 2003 to 2010 in  the tribal areas. The interventions yielded healthy marketable fruits to a distance of 500 KM. Neighborhood effect in tribal  villages motivated 260 households for mango planting in 13 hamlets of 5 Gram Panchyats (GPs) planted on an area of 588  acres under high density mode (5 X 5 m) on unused foot hills, gentle hillocks and sloppy land. The results indicated that  technological interventions through result demonstrations, social mobilization and development of marketing channel  could develop confidence among tribals for mango cultivation and thereby resulted in expansion of area under mango  cultivation. The perceived constraints of the mango farmers in tribal areas were lack of result oriented demonstrations,  motivation, marketing channel and confidence of mango growers.
Keywords: Mango; tribals; fruit fly management; hot water treatment; social mobilization